Fusobacterium necrophorum tonsillitis: an important cause of tonsillitis in adolescents and young adults - Jensen, A.; Hansen, T.M.; Bank, S.; Kristensen, L.H.; Prag, J. (Clinical microbiology and infection, 2015)
The role of Fusobacterium necrophorum in tonsillitis in adolescents and young adults was retrospectively investigated by culture examination. We compared the prevalence of F. necrophorum in 212 subjects with confirmed clinical tonsillitis and in 176 subjects with confirmed no clinical tonsillitis. The prevalence of F. necrophorum was significantly higher (p < 0.001) in subjects with clinical tonsillitis (27%) compared to subjects with no clinical tonsillitis (6%). These results clearly demonstrate the role of F. necrophorum in tonsillitis. By diagnosing and treating F. necrophorum tonsillitis with, for example, penicillin, metronidazole, or both, we might prevent some cases of Lemierre syndrome.